2014
DOI: 10.1111/roie.12135
|View full text |Cite
|
Sign up to set email alerts
|

Race‐to‐the‐bottom Tariff Cutting

Abstract: Unilateral tariff liberalization accounts for the lion's share of trade liberalization since the 1980s and has accompanied the most successful trade‐led development model of the past 50 years, “Factory Asia”. Understanding what drove this liberalization is therefore crucial to our grasp of the process of economic development. This paper provides empirical evidence for seven Asian emerging economies from 1988 to 2006 consistent with a tariff race to the bottom driven by a competition for foreign direct investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…In Blanchard (), tariff reductions spur export‐oriented foreign direct investment (FDI) and a cause a cycle of liberalization. Vezina () provides some empirical evidence for “Factory Asia countries” that is also consistent with this theoretical framework.…”
supporting
confidence: 60%
“…In Blanchard (), tariff reductions spur export‐oriented foreign direct investment (FDI) and a cause a cycle of liberalization. Vezina () provides some empirical evidence for “Factory Asia countries” that is also consistent with this theoretical framework.…”
supporting
confidence: 60%
“…He suggested that decades of unilateral tariff cutting (in order to obtain marginal locational advantages) in emerging economies of Asia have been induced, at least in part, by a competition aimed to attract FDI from Japan. Using spatial econometrics, the author showed that tariffs on parts and components, which could be considered as a crucial locational determinant for Japanese firms, followed those of competing economies if the latter were lower, if the motivation to obtain FDI was high, and when competing countries had the similar level of development [10].…”
Section: Issn 2412-8872mentioning
confidence: 99%
“…After all, this kind of unilateral action had accounted for more than two thirds of all trade liberalisation by developing countries in the two decades leading up to 2003 (World Bank 2005). There is also a host of other evidence, 6 including that of Vézina (2010), which shows that it was unilateral actions that played an overwhelming role in the trade liberalisation of the original ASEAN members, and in drawing in foreign direct investment to these countries to supplant the regional supply chain. In this way, the rise in regionalism may eventually be the most compelling factor in contributing to its own demise by revitalising multilateralisation, if not the multilateral system.…”
Section: The Way Forwardmentioning
confidence: 99%